INNOVATIVE SOCIAL WORK TECHNOLOGIES DURING MARTIAL LAW - Katerynych, Anna; Martyniuk, Yana; Kharkivska, Tetiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Innovative technologies in the field of social work play an important role in supporting the population in the conditions of martial law. Their introduction makes it possible to more effectively solve problems related to the humanitarian consequences of war and provide the necessary support to vulnerable population groups. Modern technologies can become a key tool for the work of social services in difficult conditions. A period of martial law always leads to complex challenges for society, including social aspects. Children and young people, including those with disabilities, need special attention. The authors propose to consider modern technologies as a tool for improving social work with children and young people in the conditions of martial law. An important aspect will be the results and recommendations for social sector specialists regarding their implementation. The purpose of the article is to define and substantiate innovative technologies of social work during martial law with children and youth, including persons with disabilities, and to provide recommendations for social sector specialists regarding the use of the outlined technologies in the social sector of the state and public organizations. The article is devoted to the use of innovative technologies of social work for the development of conflict-free communication skills, effective communication, leadership and creative potential, as well as the involvement of young people in volunteering and social integration.